Urbanization and urban growth in Iraq - عهود جبار عبيره (College of Education for Women, 2019)
The development issue is considered as one of the most important matters of concern to governments, intellectuals and specialists in the contemporary world, especially in developing countries that are trying hard to move out of the afflicting underdevelopment domain to a brighter future and achieve the aspirations of those countries through organized planning which take advantage of available resources, whether material or humanitarian, in the best way possible. The development process are taking place at multiple levels ranging from national to regional to local where the community is stimulated and excited for the cooperation, participation and preparation to perform planned change in the methods of thinking, acting and production.